Two-layer distributed cache in D2D integrated fog-RAN - Chengyu XIA; Yanxiang JIANG (Dianxin kexue)
With the development of mobile communications,people’s demands for low-latency transmission networks are rapidly increasing.Fog-RAN,as a new architecture suitable for 5G/B5G communication networks,has broad application prospects.Considering the fog network of device-to-device communication,a two-layer distributed cache based on device-to-device communication and fog-RAN was proposed to reduce the delay for users to download files.Firstly,a closed-form solution of the download delay of the two-layer cache and a closed-form solution of the delay gain were obtained.On this basis,a distributed algorithm was designed to obtain the best cache strategy,so that each fog-based wireless access point (F-AP) or user equipment (UE) only needed to use the information of the neighboring devices to complete the caching.The simulation results show that the two-layer distributed cache can effectively reduce the download delay.